2004
DOI: 10.1175/jas-3297.1
|View full text |Cite
|
Sign up to set email alerts
|

Solar and QBO Influences on the Timing of Stratospheric Sudden Warmings

Abstract: The interaction of the 11-yr solar cycle (SC) and the quasi-biennial oscillation (QBO) and their influence on the Northern Hemisphere (NH) polar vortex are studied using idealized model experiments and ECMWF Re-Analysis (ERA-40). In the model experiments, the sensitivity of the NH polar vortex to imposed easterlies at equatorial/subtropical latitudes over various height ranges is tested to explore the possible influence from zonal wind anomalies associated with the QBO and the 11-yr SC in those regions. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
156
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(179 citation statements)
references
References 28 publications
21
156
2
Order By: Relevance
“…Other studies have shown that in the Northern Hemisphere winter extratropics a solar signal in polar winter temperature and wind is QBOphase dependent, moving poleward and downward as winter progresses, taking about 1 month to move from the upper to the lower stratosphere with a faster descent rate under wQBO than eQBO (Matthes et al, 2004;Gray et al, 2004;Lu et al, 2009;Haigh and Roscoe, 2009) showed a similar progression in the Southern Hemisphere late winter.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Other studies have shown that in the Northern Hemisphere winter extratropics a solar signal in polar winter temperature and wind is QBOphase dependent, moving poleward and downward as winter progresses, taking about 1 month to move from the upper to the lower stratosphere with a faster descent rate under wQBO than eQBO (Matthes et al, 2004;Gray et al, 2004;Lu et al, 2009;Haigh and Roscoe, 2009) showed a similar progression in the Southern Hemisphere late winter.…”
Section: Introductionmentioning
confidence: 75%
“…We note that none of these statistical studies provides any mechanism for the apparent relationships but that the different responses might indicate where causal links occur. For example, Gray et al (2004) propose an effect of solar/QBO variability whereby a perturbation to the sub-tropical upper stratosphere might affect the polar lower stratosphere after 3-4 months through influencing the timing of sudden stratospheric warmings. Over this period the QBO phase would have descended 3-4 km in the tropics so that an instantaneous correlation between polar temperature and QBO would appear highest at lower altitudes in the tropics.…”
Section: Discussionmentioning
confidence: 99%
“…The negative zonal wind response in late northern winter may be caused by an increased likelihood of major stratospheric warmings later in the winter under solar maximum conditions when the polar vortex in early winter is stronger, on average, and therefore less susceptible to disruption (e.g. Gray et al, 2004). Since GCMs have not yet successfully simulated this pattern (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The latitudes of tropospheric jet streams have been shown to be sensitive to the solar forcing of stratospheric temperatures (Haigh 1994(Haigh , 2003Poore et al 2004). This could occur through disturbances to the stratospheric polar vortex (Gray et al 2004), which can propagate downwards to affect the tropospheric jets (Plumb and Semeniuk 2003) or through the effects of stratospheric temperature changes on stratospheric winds and the refraction of tropospheric eddies (Kushner and Polvani 2004;Simpson et al 2009). Models (e.g., Shindell et al 2001a, b) predict that perturbations can descend from the stratosphere to the surface by altering the propagation of planetary waves coming up from the surface, an effect that has been observed in data (Perlwitz and Harnik 2003).…”
Section: ''Top-down'' Solar Forcingmentioning
confidence: 99%